Técnicas innovadoras de motivación lectora y su repercusión en el rendimiento académico en los estudiantes del 7º año de educación básica de la Unidad Educativa “Caracol”, Parroquia Caracol, cantón Babahoyo, Provincia los Ríos - Jiménez Salazar, Tanya Katerine (2015)
study of this research was conducted by students of the seventh year of basic education of the Education Unit "Caracul" came to present problems in the assimilation of knowledge regarding the lack of motivation for reading, so the application was implemented Innovative Techniques reading motivation, why the Ecuadorian teachers should use them, that build on their students their own ideas; Share: Their experiences and their thinking; Criticizing: constructively own ideas of others; Fun: With all by learning more difficult as these; quiz: Correcting his own errors with the valuable help of the teacher. For the improvement of students and teachers. If the development of classroom activity is achieved practical and operational will be facing a new reality in education is a challenge where one must be ready to run, and certainly if you intend to be achieved. It is necessary that teachers not only know these attitudes, but also put into practice in their professional life to form autonomous individuals with ability, skills and values. At home foster moral, ethical and spiritual to protect their children from external influences values, the school must continue to strengthen not only the knowledge if not the rules of good behavior and values that drive the student for the right path. To have a personality that allows them to be entrepreneurial human and useful to society people.